Alternatif Ganjaran Seumpama Pahala Ibadat Haji Dan Umrah Era Pandemik Covid-19: Suatu Analisis Awal - Lukmanul Hakim Hj Hanafi; Syed Najihuddin Syed Hassan (Intelligentia Resources, 2024)
This paper aims to explain and discuss the alternatives to obtain similar rewards as hajj and umrah for Muslims or future hajj and umrah pilgrims who are obstructed to leave for the Holy Land of Mecca in the COVID-19 pandemic season, at the same time without dropping the obligation of hajj and umrah in the future. To achieve the objectives of this writing, the library method was used to collect data and content analysis was used to analyze all the documents. The study found that there are histories of the Prophet S.A.W. in the Qur'an and Hadith which explains how to obtain rewards as similar to the rewards of hajj and umrah in the practices of daily life, and also for Muslims who are unable to perform hajj and umrah in the Holy Land of Mecca but want the similar rewards of hajj and umrah. It is hoped that the findings from this research will be a ‘cure’ and 'ilāj for Muslims who are sad and unable to perform hajj and umrah in the Holy Land of Mecca and then be satisfied and think well of the planning of Allah S.W.T.. It is suggested that future researchers construct modules or models related to this study.